Gulf Islands, Trinidad (2011)
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided The postcard shows one of the "Five Islands" which are actually a group of six islands that are located west of Port of Spain, the capital of Trinidad, in the Gulf of Paria. They are also known as Las Cortorras. The Five Islands are: Caledonia Island; Craig Island; Lenagen Island; Nelson Island and Pelican Island. Rock Island is the sixth island. Funding for this project has been provided by Mrs. Irma E. Goldstraw.